Impact of Stakeholders in Business Management - Viteri Moya, Jorge (2010)
The term stakeholder refers to the people, groups or organization that may be directly or indirectly related to the company and that may be affected by its decisions or actions. The work ethic that a company has, as well as the commitment that it maintains with its stakeholders, will allow achieving a balance between the company's interest groups, anticipating the demands of society, offering quality and trust and achieving profits as an obvious result. of his actions.